Demand for long acting and permanent methods of contraceptives and factors for non-use among married women of Goba Town, Bale Zone, South East Ethiopia - Takele Abulie; Degu Getu; Yitayal Mezgebu (BMC, 2012)
Abstract Background Contraceptive use including short acting, long acting and permanent methods positively influence the socio-economic development of a nation by allowing families to space and limit their family size to their economic capacity. Demand for LAPMs of contraception as detrmined by utilization and unmet need for LAPMs of contraception can provide realiable information for providers. Objective To determine the utilization of long acting and permanent contraception and its associated factors among married women of Goba town, South East Ethiopia. Methods A cross sectional community based study was conducted among 734 systematically selected married women of reproductive age in Goba town in September/ 2009. A structured and pretested, interview questionaire was used to collect data on socio-demographic, behavioral factors and data related to demand for LAPMs of contraception. Data were analyzed using EPI INFO and SPSS version 16. Result The demand for Long Acting and Permanent Methods (LAPMs) of contraception was 18.1%. Utilization of LAPMs of contraception in the town was 64 (8.7%) and the unmet need for LAPMs was 69 (9.4%). Information on LAPMs in the town was 636 (86.6%). Media (radio and television) was the major sources of information 641 (87.3%). The use of LAPMs was significatly associated with ever use AOR[17.43, 95% CI:9.19, 33.03], number of times discussions made on methods AOR[4.6, 95% CI: 1.72,12.17] and main decider of using methods AOR[ 2.2, 95% CI:1.03, 4.65]. It was not associated with socio-demographic variables. Conclusion and recommendation The utilization of LAPMs in the town was less although higher than the Ethiopian demographic and health survey 2005 result. Moreover, there was a considerable unmet need. Increase the method mix of LAPMs by incorporating varaies of implnats in order to increase utilization. Proper counseling of client and partners discussion were some of the recommendation forwarded.